Pengaruh Pertumbuhan Wisatawan terhadap Kualitas Udara di Kota Yogyakarta (Sebuah Kajian Literatur) - Uul Resia Harahap; Gunawan Wibisono; Ahmad Zaenudin; Juli Kristiarina Susanti (Program Studi Pembangunan Masyarakat Desa (D3), 2025)
The rapid growth of tourism in Yogyakarta has brought significant economic benefits but also raised concerns about environmental impacts, particularly air quality degradation. This literature review aims to analyze the relationship between tourist growth and air quality through a systematic examination of existing studies from 2015-2024. Using systematic literature review methodology, 28 peer-reviewed articles, government reports, and relevant publications were analyzed from multiple databases. Key findings indicate that increased tourist activities contribute to elevated levels of particulate matter (PM2.5 and PM10), nitrogen oxides (NOx), and carbon monoxide (CO) concentrations, particularly in popular destinations such as Malioboro Street, Sultan Palace area, and Taman Sari. Monitoring data shows PM2.5 concentrations ranging from 45-65 μg/m³ in tourist areas, frequently exceeding WHO standards. Primary pollution sources include increased vehicular traffic with 200-300% volume increase during peak seasons, emissions from tourist transportation, hotel operations contributing to 20-40% higher energy consumption, and intensified commercial activities. The relationship is complex, influenced by seasonal variations, meteorological conditions, and urban planning policies. Temporal analysis reveals pollution peaks during school holidays and special events, with daily peaks between 16:00-19:00 when tourist activities coincide with rush hour traffic. The study concludes that sustainable tourism management strategies are urgently needed, including sustainable transportation development, tourist capacity management, and green tourism initiatives to balance economic growth with environmental preservation in Yogyakarta